2009
DOI: 10.1097/gme.0b013e31817d5372
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal estradiol gel 0.1% for the treatment of vasomotor symptoms in postmenopausal women

Abstract: Low-dose transdermal estradiol gel 0.1% is an effective treatment for relief of vasomotor symptoms, as well as signs of vulvar and vaginal atrophy, associated with menopause. Estradiol gel 0.1% offers multiple dosing options to individualize patient therapy, including the lowest available effective dose (0.25 mg estradiol, delivering 0.003 mg/d estradiol) to treat the vasomotor symptoms of menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
1
15
0
1
Order By: Relevance
“…9,18 Lower than standard doses of HT have been shown to effectively reduce VMS, relieve vulvovaginal symptoms, and preserve bone mineral density nearly equivalently to standard doses, with lower rates of side effects. [18][19][20]28 However, lower doses have not been tested in long-term studies. 18 There is no clear guidance for the most appropriate way to approach HT discontinuation, although evidence suggests that most women will experience recurrence of at least one menopausal complaint, most often VMS, regardless of whether HT is stopped abruptly or tapered.…”
Section: Pharmacologic Optionsmentioning
confidence: 98%
See 1 more Smart Citation
“…9,18 Lower than standard doses of HT have been shown to effectively reduce VMS, relieve vulvovaginal symptoms, and preserve bone mineral density nearly equivalently to standard doses, with lower rates of side effects. [18][19][20]28 However, lower doses have not been tested in long-term studies. 18 There is no clear guidance for the most appropriate way to approach HT discontinuation, although evidence suggests that most women will experience recurrence of at least one menopausal complaint, most often VMS, regardless of whether HT is stopped abruptly or tapered.…”
Section: Pharmacologic Optionsmentioning
confidence: 98%
“…9,17 Lower doses may reduce the risk of irregular bleeding and breast tenderness. 19,20 Findings from the WHI primary prevention trial revealed long-term use of HT at high doses in populations consisting of older postmenopausal women (mean age at baseline, 63 years) 21 to be associated with an increased risk of thromboembolic events, stroke, coronary heart disease (CHD), cardiovascular events, increased mammographic density, and increased risk of breast cancer diagnosis. 21,22 However, the degree of risk, particularly for CHD, may vary with time of initiation and duration of therapy.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…43 Lower doses may also require longer duration of therapy for full benefit to manifest. 44 These limitations are acceptable for many women, especially when coupled with expectations (although not yet proven in RCT) for improved safety with the use of lower-dose MHT regimens. For those whose symptoms are not adequately treated with lower-dose formulations, MHT doses can be slowly (every few months) titrated upward until symptom relief is achieved.…”
Section: Consider Lower Dosesmentioning
confidence: 97%
“…In the United States, there are three doses: 1.0, 0.5, and 0.25 g. E 2 gel 0.1%, which received US FDA approval based on the results of a positive phase III clinical trial. 17 In this trial, a total of 488 postmenopausal women with a median age of 54.6 years, who had undergone …”
mentioning
confidence: 99%